Ruthenium p‐Cymene Iminophosphonamide Complexes: Activation under Basic Conditions and Transfer Hydrogenation Catalysis. Issue 20 (20th February 2018) - Sinopalnikova, Iana S.; Peganova, Tatyana A.; Belkova, Natalia V.; Deydier, Eric; Daran, Jean‐Claude; Shubina, Elena S.; Kalsin, Alexander M.; Poli, Rinaldo
Abstract : Complex [(η 6 ‐Cym)RuCl(NPN )] {Cym = p ‐cymene;NPN = ( p TolN)2 PPh2 } (1 ) yields a thermally sensitive hydride derivative [(η 6 ‐Cym)RuH(NPN )] (2 ) by reaction with i PrOH in the presence of a strong base, via an observable isopropoxide intermediate [(η 6 ‐Cym)Ru(O i Pr)(NPN )] (3 ), or with NaBHEt3 in toluene. Partial conversion also occurs in i PrOH in the absence of base.2 is stabilized by dihydrogen bonding with isopropyl alcohol, but attempts to isolate it induce isomerization by hydride migration to a ring CH position to yield a 16‐electron cyclohexadienyl derivative [{η 5 ‐ p ‐C6 H5 (Me)( i Pr)}Ru(NPN )], which has been crystallographically characterized as a disordered mixture of two regioisomers (4 /4′ ). Complex2 is able to release H2 upon treatment with medium strength proton donors (fluorinated alcohols), but also slowly with i PrOH.2 is an active catalyst for the transfer hydrogenation of acetophenone to phenylethanol in isopropyl alcohol. The catalytic transformation is first order in acetophenone and first order in catalyst, with k = 117 ± 10m –1  h –1 at 40 °C. The temperature dependence of the rate constant (25–80 °C) gave the activation parameters Δ H ‡ = 9.6 ± 1.3 kcal mol –1 and Δ S ‡ = –31 ± 4 cal mol –1  K –1 . DFT calculations have validated the slow isomerization of2 to4 /4′ (high energy TS), the preference of the cyclohexadienyl system for4 /4′ relative to the other isomers4 Me and4 i Pr, where the hydride has migrated to the CMe or C i Pr position, and suggest that the hydrogen transfer mechanism involves outer sphere hydride transfer to the ketone substrate with H‐bonding assistance of isopropyl alcohol to yield a σ complex intermediate [(η 6 ‐Cym)Ru + (NPN ){H‐C(Me)(Ph)O – }]. Abstract : A highly reactive arene ruthenium iminophosphonamide hydride complex catalyzes acetophenone transfer hydrogenation by isopropyl alcohol via a proposed zwitterionic intermediate and rearranges to a cyclohexadienyl 16‐electron complex in the absence of substrate.